Assessment of Burkholderia glumae control in rice (Oryza sativa) FEDEARROZ 67, using silver nanoparticles (AgNPs) under greenhouse conditions (2023)
Bacterial panicle blight, caused by Burkholderia glumae, represents a significant threat to global rice production, jeopardizing future food security. The severity of this seed-borne disease has been amplified by shifting environmental conditions, yet effective control strategies and fully-resistant rice varieties remain elusive. This research was conducted with the FEDEARROZ 67 rice variety sourced from Agua Clara, Cucuta municipality, and tests were undertaken under controlled greenhouse conditions at Universidad Francisco de Paula Santander. Our objective was to assess the potential of electrochemically synthesized silver nanoparticles (AgNPs) for controlling B. glumae. We employed a completely randomized design with five treatments: preventive, curative, positive control, negative control, and absolute control. Variables analyzed included the number of chlorotic leaves, plant height, and weight. Statistical analyses encompassed variance analysis and Tukey's mean comparison tests using XLSTATS version 2018. Our findings revealed that the preventive treatment with AgNPs at a 5 ppm concentration exhibited significant phytoprotective effects against B. glumae. Plants under this treatment showcased fewer chlorotic symptoms and greater heights and weights compared to controls. These findings underline the potential of nanotechnology as a groundbreaking tool for combating bacterial diseases in essential crops such as rice, thereby contributing to a sustainable future for global agriculture.